Ragam Bahasa Bias Gender pada Pemberitaan Aktris Pascacerai - Yuliana Jetia Moon; Antonius Nesi; Ans Prawati Yuliantari (Jurnal Semantik, 2023)
Language can perpetuate gender bias. The formulation of language in media coverage also strengthens, soothes, even injustices against women in society, including actresses. The purpose of this research is to find and describe the variety of gender bias language in the reporting of post-divorce actresses. This research includes a qualitative descriptive study. The data source for this research is media coverage which is limited to news about post-divorce actresses. The data taken is in the form of gender biased news titles and contents. In collecting data using the read-read method, supported by orthographic techniques. Furthermore, the data were analyzed using constructivism analysis in sociolinguistics. The results of this study indicate that there are still media that place divorced actresses as news objects that are sexy and gender biased. The variety of language gender bias appears in the form of diction, phrases and sentences. These various forms of language can position women as sexual objects, such as various metaphors that refer to women's bodies, diction and sentences that point to the meaning that women are the cause of household breakdown, as well as various languages ​​in the form of labeling women or stigmatization.